The Lifelong Learning Link: Twelve Reasons for Continuous Education for Missionaries - Brewer, Monroe (Missiology, 1991)
By planning for growth on all levels—personal, cultural, and organizational—missionaries can help correct errors of the past; can learn better; can more creatively interact with life situations; can be more flexible, relevant, and stimulating in their ministries; can have lives more fully integrated and balanced; can potentially have fewer and less serious problems and not stagnate in their missionary ruts; and can be a blessing to everyone else and God too.This article presents the case for a commitment to “continuous education” by proposing four philosophical and eight practical reasons for missionaries to expand their ministries through lifelong learning.